Pengaosan Al Qur’an within Tingkeban Tradition in Trenggalek, Indonesia - Hanif, Aulia; Ubaidillah, Ubaidillah; Marpuah, Siti (KARSA Journal of Social and Islamic Culture, 2024)
The physiological-biological experience of women from pregnancy to childbirth does not only involve carrying and giving birth to a child but also a spiritual journey, faith, and humanity. The essence of spirituality is actualized in the Javanese tradition known as tingkeban, which can potentially encourage social, emotional, and personal change. This analytical descriptive research aims to reveal the process of tingkeban tradition as a form of acculturation of Javanese Islam and social changes. This study used data collection methods from documentation, observation, and interviews using Karl Mannheim's sociological approach in the reception of objective, expressive, and documentary values to reveal the meaning in society. As a result, it is known that historically, the practice of tingkeban tradition in Pesantren Darussalam is a Javanese tradition passed down as a slametan for a sort of baby shower ceremony reformulated into Islamic values with recitation of some verses of eight selected surahs, namely Yusuf, Maryam, Al Kahfi, Yasin, Taha, Al Waqi'ah, and Ar Rahman. These selected surahs symbolize the hope of success for future children, joy and friendship, and smoothness in the baby delivery process. It is known that the tradition of tingkeban has created a psychological-spiritual impression on the fadhilah (advantage) of reading the surah to strengthen social and spiritual integration in the form of the Khotmil Qur'an tradition taking place twice a month between wage for fathers and legi for mothers.